THE ISLAMIC VALUES BASE NATURAL SCIENCES INSTRUCTIONAL MATERIALS DEVELOPMENT MODEL - Rusydi Ananda (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2018)
The object of this research was to develop of instructional materials model of the natural science based on Islamic values. Expansion of this research had been implementing the research method of Research &Development. The results of the validation of expert’s team concluded that the model meets the instructional materials designed just and proper procedures were used. Based on the results of the feasibility test was then followed by one-to-one learner, small group and field trials. Then test the effectiveness of the model were by comparing the results of pretest and posttest and were analyzed using t-test. It was concluded that the instructional materials products give a real effect on student learning outcomes.